THE ARTICULATION OF MULTICULTURAL PRINCIPLES OF BOARDING SCHOOL IN EAST LUWU REGENCY - Rahmat Rahmat (Jurnal Adabiyah: Humanities and Islamic Studies, 2018)
AbstractThis study discusses about the part of research on the implementation of the multicultural education of Islamic boarding schools in East Luwu Regency, namely the meaning of multicultural principles. There are three main principles in the concept of multiculturalism, they are; the principle of openness, moderation, and unity in difference. The principle of openness is understood by the boarding school as an opening door for anyone in various activities. The principle of moderation is a principle that brings together differences that occur in society. And the principle of unity in difference is the principle of establishing multicultural relationships. Keywords: multicultural principles, Boarding school, and East Luwu Regency AbstrakKajian ini membahas tentang bagian dari penelitian implementasi  multikultural pada pesantren di Kabupaten Luwu Timur, yaitu pemaknaan prinsip-prinsip multikultural. Ada tiga prinsip utama dalam konsep multikulturalisme, yaitu prinsip keterbukaan, moderasi, dan bersatu dalam perbedaan. Perinsip ketebukaan dipahami pihak pesantren sebagai pintu membuka diri kepada siapa saja dalam berbagai aktivitas. Perinsip moderasi merupakan prinsip yang mempertemukan perbedaan yang terjadi di tengah-tengah masyarakat. Dan prinsip bersatu dalam perbedaan adalah prinsip untuk menjalin silaturahmi multikultural.Keywords: Prinsip-prinsip multikultural, pesantren, dan Kabupaten Luwu Timur